Fungal Diversity in the Mediterranean Area - Venturella, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Fungi are important components of ecosystems. Their level of diversity is very high and only lower than that of insects. This book deals with fungal diversity in the Mediterranean, a large area recognized as a biodiversity hot spot. Micro and macrofungi contribute to characterizing many environments, both terrestrial and marine, in which they are associated with particular forest stands and also contribute to providing plant and soil nutrients. They also show potential applications in the medical and pharmaceutical fields, have a recognized nutritional and commercial value and still provide many insights to scholars in terms of description of new species and actions aimed at in situ and ex situ conservation.